Huge Renal Hydatid Cyst- an Unusual Presentation: A Case Report - Jafari Nodoushan, Jamal; Zare, Samad; Tabatabaei, Seyed Mostafa; Babaei Zarch, Mojtaba; Imani, Fatemeh; Ehsani, Fatemeh (Urology Journal, 2017)
Isolated renal hydatid cyst is a rare entity accounting for only 2-4% of cases. A 60-year-old male presented to our clinic complaining of pain in right flank. He had a history of eating raw sheep liver. Imaging revealed an expansive cystic mass measuring approximately 300×180 mm in the right side of abdomen. The patient was treated by open surgery in combination with perioperative chemotherapy with albendazol. In this case, we reported an unusual presentation of hydatid cyst disease. Physicians should be aware of its clinical presentations and complications.